Role And Function Of Attorney In Order To Optimize The Prevention Of Corruption Through Establishment Of TP4P/D (Case Studies In State Attorney Of Grobogan) - Abdul Haris; Umar Ma'ruf (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Corruption or rasuah is the act of a public official, either politicians nor government employees, as well as other parties involved in the action that is not fair and does not legal. It is very necessary to do eradication and prevention in a planned and measured by the Government. The purpose of this study was to describe, assess and analyze on the Role and Functions of The Attorney in Order to Optimize the Prevention of Corruption Through The Establishment of The Guards and Security Governance and Development Center / Regional (TP4P / D). This study uses empirical juridical approach, with specification of descriptive analytical research. The data used in this research is secondary data obtained through library research and primary data obtained through field research were then analyzed qualitatively Policy Implementation theory, and the theory of the authority. The results of this study are: Role and Functions of the Attorney in order to optimize the Prevention of Corruption through the establishment of the Guards and Security Governance and Development Center / Regional (TP4P / D) is not an assignment and new functions given to the Attorney of the Republic of Indonesia, duties and functions TP4P / D preexisting regulated in Act No. 16 of 2004 concerning the Attorney RI and has been written in the Regulation of General Attorney of the Organization and Work Procedure Attorney of the Republic of Indonesia. Keywords: Prevention; Corruption; Attorney RI.